Covid-19 Pandemic: Towards the “New Normal” among Malaysian Public Universities - Nurul Naimah Rose, Aida Shakila Ishak, Nor’izzah Ahmad (International Journal of Advanced Science and Technology, 2020)
The pandemic of Corona Virus (Covid-19) in Malaysia had affected so many sectors including the education sectors. To prevent the spread of this virus, the Malaysian government launched the enforcement of the movement control order which then further extend with the conditional movement control order. The enforcement has forced the public universities to comply with the standard operation of the procedure (SOP) within the university compound. Therefore, the aim of this study to examine the ways of Malaysian public universities reacted to the rules of MCO and CMCO during the Covid-19 pandemic. The conceptual analysis methodology is used in this study to imply secondary information from various sources such as the internet, newspapers and government published sources. The major findings showed that Malaysian public universities immediately respond to the enforcement by closing the campus, banning students and staffs from travel overseas, postponing all physical classes, lab and workshop. The teaching and learning shift to virtual classes and all staffs required to use online platform for meetings, communications and completing the task. Moreover, this paper also discussed the psychological impact among students as well as health and counselling support provided that helps students during the pandemic. In conclusion, this paper suggested that Malaysian public universities need to be well prepared to face upcoming challenges in adapting the new normal of education systems during and post Covid-19 pandemic. Keywords: Covid-19, MCO, Malaysian Public Universities, online learning, health and psychology